Pengaruh Customer Relationship Manajemen dan Kualitas PelayananTerhadap Kepuasan Pasien serta Dampaknya kepada Loyalitas Pasien Non BPJS - Wahono Sumaryono; Derriawan; Faizah (JRB-Jurnal Riset Bisnis, 2020)
Puskesmas as a First Level Health Facility that provides individual health services and community health services, is responsible for its working area. Public health efforts are made to increase public knowledge of the quality of health services it receives. This study aims to determine the activities of Customer Relationship Management and service quality that can affect patient satisfaction and its impact on patient loyalty of non-Social Security Administering Bodies (BPJS) at the Pasar Rebo District Health Center and the Kramat Jati District Health Center. This research method is a survey method. The selection of respondents was carried out using random sampling techniques on non-BPJS patients at the Kramat Jati Subdistrict Health Center and Pasar Rebo District Health Center and primary data was collected using a validated questionnaire. The research approach is quantitative descriptive and statistical data analysis of research results using Structural Equation Modeling. Data analysis from 200 completed questionnaires that meet the inclusion criteria. Based on the results of the study, the path coefficient value on patient satisfaction is Customer Relationship Management of 0.266, service quality of 0.773, while the results of research on patient loyalty are Customer Relationship Management of 0.270, service quality of 0.191 and patient satisfaction of 0.421. Effective Customer Relationship Management, good service quality and high patient satisfaction can increase patient loyalty.